A long-term drought reconstruction based on oxygen isotope tree ring data for central and eastern parts of Europe (Romania) - V. Nagavciuc; V. Nagavciuc; G. Helle; M. Rădoane; C.-C. Roibu; M.-G. Cotos; M. Ionita; M. Ionita (Biogeosciences)
This study investigates the relationship between oxygen isotope ratios (δ18O) in oak tree ring cellulose and past drought variability in Letea Forest, Romania. A δ18O site chronology spanning 1803–2020 was compiled from seven individual time series. δ18O values exhibited a significant negative correlation with moisture-related variables (cloud cover, relative humidity, and precipitation) and a positive correlation with temperature and sunshine duration. This confirms that δ18O from tree rings can be a good proxy for moisture availability. The strongest correlation was found between δ18O and the August Standardized Precipitation Evapotranspiration Index for an accumulation period of 9 months (SPEI9) for central and eastern Europe. This highlights SPEI9 as a superior indicator of drought compared to individual parameters like temperature or precipitation. Using a linear regression model, we reconstructed August SPEI9 variability for the past 200 years. The reconstruction captured interannual and decadal variations, with distinct wet and dry periods. Analysis of large-scale atmospheric circulation patterns revealed a link between high δ18O values (indicating dry conditions) and a high-pressure system over the North Atlantic. Conversely, low δ18O values (indicating wet conditions) corresponded to negative pressure anomalies over Europe. Moreover, extreme values of δ18O are also associated with the prevalence of a hemispheric teleconnection pattern, namely wave number 4. This δ18O chronology and the corresponding August SPEI9 reconstruction offer valuable tools for understanding past climate variability and its relationship with large-scale atmospheric and oceanic circulation patterns.